A planning error revealed: Mother Tongue education (1998–2010) in Hong Kong. Issue 2 (October 2016) - Chu, Edward Y.W.
Abstract : This paper evaluates the exceptionally forceful "mother-tongue" (MT) education policy in force in Hong Kong from 1998 to 2010, where instruction, print materials and assessments were required to be done in students' first language, Chinese. Apart from relevant literature, a number of sources are searched, including the quantitative data obtained from the Hong Kong Examination and Assessment Authority (HKEAA), qualitative data of surveys, and the official documents commissioned by the Education Bureau (EDB) within the period. While MT education has arguably minimized mixed-code teaching in content subjects, there is clear evidence that it failed to raise L2 standard through specialized teaching as promised. Much more students off the top tier being denied for admission to university, the principle of equality of educational participation is violated. A postmortem analysis, drawing on the more recent findings from the field of applied linguistics, shows that the adoption of bifurcation medium of instruction model and the ineffective L2 exposure are the culprits. All this, together with the lack of monitoring of the policy in its initial stage, are speculated as the major causes of its failure.